MCA: It’s Implementation Based on Teachers’ Perspective - Agus Supramono; Heri Retnawati (Universitas Pendidikan Ganesha, 2023)
Minimum Competency Assessment (AKM) is one of Indonesia's newest National Assessment instruments for students' literacy and numeracy competencies. In policy implementation, the teacher is the spearhead in preparing students for AKM. This study aims to analyze the teacher's perspective in dealing with AKM. This phenomenon is studied through phenomenological-type qualitative research. Data collection was carried out through semi-structured interviews. The participants in this study were fifth-grade elementary school teachers. A total of 11 participants were recruited voluntarily. Qualitative data analysis was carried out using the Bodgan and Biklen model, with data reduction, data presentation, and conclusion. The study results show that teachers' confusion in preparing for MCA is caused by; first, teachers' understanding of AKM still needs to be improved and seems partial. Second, the ability of students to show unpreparedness in terms of skills in working on computer-based problems. Third, the condition of facilities and infrastructure in schools needs to be improved. In preparing for the implementation of AKM, teachers are faced with problems originating from aspects of teachers, students and facilities and infrastructure.